EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI KACANG TANAH (Arachis hypogaea L) DI KECAMATAN TANON KABUPATEN SRAGEN - ARI SUSANTO; SUTARNO SUTARNO; SUBAGYO SUBAGYO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2011)
This research was carried out on FebruariÂ to April 2008. The aim of this research is to knowing the production factors, which is fluential to Bean production, the efficiency of using production factors and the amount of the cost, and the income of Bean operation. The main method used is analytical description and is the realization used survey method. The location determination with purposive, the determination of sample number of farm with proportional random sampling. The process of data collecting done by some interview with the farmers using questioner. The method of data analysis Cobb Douglas type, and efficiency analysis. Result of production analysis indicator using wide production area factor, labor force, seed, Urea fertilizer, Phonska fertilizer, KCl fertilizer, Antabrone pesticide, education, and experience together influential to Bean production. Trial result indicate wide production prouction area labor force, seed, Urea fertilizer, Phonska fertilizer, KCl fertilizer, Antabrone pesticide, education, and experience is very significant. From the efficiency analysis result we could get result that using of production factor on Bean farm operation has not reached the optimum combination or hasnâ€™t get high economical efficiency using. Using wide age, area, labor force, seed, Urea fertilizer, Phonska fertilizer, KCl fertilizer, Antabrone pesticide efficiency not yet. The average of farm revenue income brutto is Rp. 6.119.755,- (Rp. 10.333.622,-/ha),the average of farm revenue is 8.285.290,-(14.042.865,-/ha), the average income netto is Rp. 2.165.535,- (Rp. 3.709.242,-/ha).